The Fragile X Proteins Differentially Regulate Translation of Reporter mRNAs with G-quadruplex Structures. Issue 2 (30th January 2022) - Edwards, Madison; Joseph, Simpson
Graphical abstract: Highlights: A minimal reporter RNA was used to test FXPs' translation regulation of mRNAs. All three FXPs bind naturally occurring G-quadruplexes from human mRNAs. FMRP's RGG motif is necessary for binding to G-quadruplex RNAs. FXR1/2P globally inhibit translation irrespective of binding to the mRNA. FMRP's inhibition of translation correlates with its binding to mRNA. Abstract: Fragile X Syndrome, as well as some manifestations of autism spectrum disorder, results from improper RNA regulation due to a deficiency of fragile X mental retardation protein (FMRP). FMRP and its autosomal paralogs, fragile X related proteins 1 & 2 (FXR1P/2P), have been implicated in many aspects of RNA regulation, from protein synthesis to mRNA stability and decay. The literature on the fragile X related proteins' (FXPs) role in mRNA regulation and their potential mRNA targets is vast. Therefore, we developed an approach to investigate the function of FXPs in translational control using three potential mRNA targets. Briefly, we first selected top mRNA candidates found to be associated with the FXPs and whose translation are influenced by one or more of the FXPs. We then narrowed down the FXPs' binding site(s) within the mRNA, analyzed the strength of this binding in vitro, and determined how each FXP affects the translation of a minimal reporter mRNA with the binding site. Overall, all FXPs bound with high affinity to RNAs containing G-quadruplexes, such as Cyclin Dependent Kinase Inhibitor p21 and FMRP's own coding region. Interestingly, FMRP inhibited the translation of each mRNA distinctly and in a manner that appears to correlate with its binding to each mRNA. In contrast, FXR1P/2P inhibited all mRNAs tested. Finally, although binding of our RNAs was due to the RGG (arginine-glycine-glycine) motif-containing C-terminal region of the FXPs, this region was not sufficient to cause inhibition of translation.